ANALISIS FRAUD BANK, PENEGAKAN HUKUM PERBANKAN, DAN PERAN OJK DALAM PENGAWASAN BPR - Danny Trisno Susetyo; Aditya Fajri Kurnia Pradana (JUNAGARA: Jurnal Ilmiah Hukum dan Kenegaraan, 2024)
Banks serve as intermediaries between savers and borrowers, collecting funds from the public and providing credit. To maintain trust, banks must apply prudential banking principles in lending, including knowing who the prospective debtor is through the "know your customer" principle. However, despite there being no national economic turmoil or mass withdrawal of funds, many People's Economic Banks (BPRs) have closed over the past decade, with 233 closures. This is mainly because BPRs are mostly local or regional in nature and susceptible to fraud. Savings and loan cooperatives have also faced issues, leading to customer demonstrations. This study aims to assess the effectiveness of the OJK supervisory function in preventing fraud in BPR banks. The researchers examine the internal control system's role in fraud prevention and assess the effectiveness and significance of OJK supervision on BPR performance. The study reveals that weak internal control systems and ineffective OJK supervision are the main causes of BPR closures.